Pelaksanaan Rekrutmen Guru dalam Meningkatkan Mutu Pendidikan Al-Qur’an di Taman Pendidikan Al-Qur’an Roudlotul Jannah Desa Jambangan Kecamatan Candi Kabupaten Sidoarjo - Rifa Syahda Kamila; Fathul Fauzi (Jurnal Budi Pekerti Agama Islam, 2025)
The main objective of this study is to provide an in-depth understanding of the implementation of teacher recruitment and the influencing factors at TPQ Roudlotul Jannah. To answer the above problems comprehensively, the researcher uses a qualitative method approach with a type of qualitative descriptive research. Data collection techniques involve in-depth interviews, observations, and documentation. In this technique, the researcher does not actively play a role in organizational activities. In addition, to ensure the validity of the data, checks are carried out through data triangulation after the data is collected and then analyzed in depth. The results of the study show that (1) the Roudlotul Jannah TPQ institution has its own system in the recruitment of teachers. The recruitment process at TPQ Roudlotul Jannah is that the system for disseminating announcements uses internal methods by word of mouth, as well as the selection process at TPQ Roudlotul Jannah they collaborate with the central institution of Qiroaati to select qualified teachers. (2) the supporting factors of the recruitment process at TPQ Roudlotul Jannah are external factors, namely the personal desire to become a TPQ teacher.